Ai Based Intelligent Security Assistant Based Virtual Ethical Hacker - M. Kumaran, E. Uvashakthi, S. Kavitha, S. Selvakumaran, P. S. Satheesh, M. Pavithra Rao (International Journal of Control and Automation, 2020)
As soon as we hear that phrase, our minds are transported into the Iron-man suit where Tony speaks to JARVIS. Though AI hasn’t really come to that level, it still shines through the everlasting limelight of several technological advancements. Assisting users in performing their everyday tasks is the main goal of any personal assistant out there. Many such applications are being developed, which are capable of discovering the user’s habits, abilities, preferences, goals, and even accurately predict the user’s actions in advance and perform them without the user's interaction. Many companies have established various kinds of AI Assistants based on their applications and areas, such as Microsoft’s Crotona, Apple’s Siri, Amazon Alexa, Google Assistant, etc. Nowadays, Hackers have become worldwide menace. Cyber security has acquired a phenomenal role in today’s scenario where we can fight against Cyber-attacks. The implementation of security techniques on their own is a tedious task. It takes a lot of time and work. Thus, in this proposal, our approach is to integrate security services in an AI assistant, thus making it an intelligent security buddy. It would thus provide several security features such as network scanning, DDOS scanning, etc. as a part of the Assistant’s characteristics. Thus the Assistant not only serves as a personal Assistant but also as a Smart Firewall and a Virtual Ethical Hacker.